Comparison Among Three Lines of Quail for Egg Quality Characters - Hassan, Asia M.; Mohammed, Dejeen A.; Hussein, Khabat N.; Hussen, Shekhmous H. (Science Journal of University of Zakho, 2017)
A total of 300 eggs from 45 female quails from three different lines (Dark brown, light brown and white) aged 10 weeks old were equally divided into three experimental groups having 15 birds of each and caged separately, to estimate the external and internal egg quality traits. Half eggs were measured 24 hrs. post lay and others were measured after one week of storage at room temperature. The results showed that there were significant differences among lines for egg length, yolk height, yolk index, albumen diameter, albumen index and Haugh unit. The light brown line resulted in the best quality. All internal egg quality characters and egg length were differed significantly between fresh and storage eggs. The fresh eggs resulted in better quality than stored eggs. Phenotypic correlation appeared that there were significant correlation coefficients between some egg quality characteristics in dark brown line more than light brown and white lines.
Keywords: Egg Quality; Lines; Storage; Quail